Munis (2011)
Documentary on Munis (Manuel Fernández Grandizo y Martinez) with: Eulogio Fernández, Luis Blanco, Agustin Guillamón, Gerard Caseras, Octavio Mondelo, Marcelo López, Pierre Degret, Neus Izquierdo, Teresa Izquierdo. Subtitles in French and English.